Physicochemical Characteristics of Nanocalcium Extract from Bones of Yellowfin Tuna (Thunnus Albacares) - Wiyan Viyata Prinaldi; Pipih Suptijah; Uju Uju (Jurnal Pengolahan Hasil Perikanan Indonesia, 2018)
Fish bone calcium is known to have good bioavailability and can be used as a natural calcium source. This study was aimed to compare the physicochemical characteristics of nano-calcium from yellowfin tuna (Thunnus albacares) obtained by three different extraction methods: milling, acid and alkaline. The research was divided into three stages: preparation of bone powder, production ofnano-calcium from fish bone and characterization of the physicochemical properties of bone powder and nano-calcium. Acid extracted nano-calcium was found to have better properties as compared to that extracted by milling and alkaline as indicated by the degree of whiteness 92.61%, moisture content 0.33%, ash 99.03%, protein 0.19%, fat 0.22%, particle size 259 nm, calcium content 83.25% and phosphorus 9.65%. The Fourier Transform Infrared (FTIR) spectra profiles indicated the presence of phosphate group (PO43-) suggesting the nano-calcium was in the form of calcium phosphate apatite.